2008
DOI: 10.2113/gseegeosci.14.4.297
|View full text |Cite
|
Sign up to set email alerts
|

Debris Basin and Deflection Berm Design for Fire-Related Debris-Flow Mitigation

Abstract: Debris flows are hazardous because of their poor predictability, high impact forces, and ability to deposit large quantities of sediment in inundated areas. To minimize the risk to developments on alluvial fans, debris-flow mitigation structures may be required. This study reviewed the state of practice for the design of two types of debris-flow mitigation structures: basins and deflection berms. Published guidelines for these structures are rare, and there appears to be little standardization. Recommended des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 32 publications
1
16
0
1
Order By: Relevance
“…These results confirm the general rule of greater debris-flow hazard during the first 2 years following a fire as postulated by Cannon et al (2011) and reflected in the reported occurrence of post-fire sedimentation in southern California (Santi and Morandi, 2013). Emergency-response personnel and land managers are increasingly aware of the immediate need to quickly institute appropriate mitigation measures to protect lives and property at risk from post-fire debris flows (DeGraff 1994;Prochaska et al, 2008;Lancaster et al, 2014;McCoy et al, 2016).…”
Section: Post-fire Debris-flow Hazard Potentialsupporting
confidence: 77%
“…These results confirm the general rule of greater debris-flow hazard during the first 2 years following a fire as postulated by Cannon et al (2011) and reflected in the reported occurrence of post-fire sedimentation in southern California (Santi and Morandi, 2013). Emergency-response personnel and land managers are increasingly aware of the immediate need to quickly institute appropriate mitigation measures to protect lives and property at risk from post-fire debris flows (DeGraff 1994;Prochaska et al, 2008;Lancaster et al, 2014;McCoy et al, 2016).…”
Section: Post-fire Debris-flow Hazard Potentialsupporting
confidence: 77%
“…They are typically 0.8 m high or less and may be pinned to the ground with steel stakes, thereby increasing resistance against sliding or overturning. No standard designs have been published, but VanDine (1996), Lo (2000) and Prochaska et al (2008b) suggest calculations for impact forces and debris run-up heights. Fig.…”
Section: Channelizationmentioning
confidence: 99%
“…Calculations for many of the input parameters required for design are summarized in Lo (2000). Complete design procedures are given in Prochaska et al (2008b).…”
Section: Channelizationmentioning
confidence: 99%
“…These results compared favorably with those generated by an existing volume model. This As a result of these and similar events, a concerted effort has been undertaken among geoscientists to detail the physical behavior and impact of debris flows: from identification of triggering mechanisms and the probability of their occurrence (Cannon et al, 2010), to mitigation measures (Prochaska et al, 2008), and to their effect on local populations (Santi et al, 2011). Debris flows pose an especially significant hazard in burned areas, as the loss of vegetation and development of hydrophobic soils increase the potential for catastrophic events.…”
mentioning
confidence: 99%
“…Currently, some of the most effective event-management designs include deflection berms (Prochaska et al, 2008), catchment basins (Gatwood et al, 2000), debris rakes, and channel enlargement (Huebl and Fiebiger, 2005). The design criteria of each of these methods are based on the largest event that is expected to occur in the lifetime of the structure (the "design event").…”
mentioning
confidence: 99%